2014
DOI: 10.1002/mame.201400207
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization of Demineralized Dentin Induced by Amine‐Terminated PAMAM Dendrimer

Abstract: The remineralization of demineralized dentin with biomimetic templates is of great interest in the fields of material science and stomatology. Amine‐terminated PAMAM dendrimer (PAMAM‐NH2), which possesses a highly ordered architecture and many calcium coordination sites, may be a desirable template for inducing dentin remineralization. In this study, the remineralization effect of the third generation PAMAM‐NH2 (G3‐PAMAM‐NH2) on demineralized dentin is investigated. Demineralized dentin samples are treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 27 publications
3
59
1
Order By: Relevance
“…In our previous studies, we successfully remineralized demineralized dentin with PAMAM dendrimers. [27,28] However, we only remineralized partially demineralized dentin and intrafibrillar remineralization was not observed due to the limitations in our detection system. In some clinical situations (i.e., hybrid layers created by etch-and-rinse adhesive systems), dentin surfaces are completely demineralized, which results in the exposure of type I collagen fibrils.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…In our previous studies, we successfully remineralized demineralized dentin with PAMAM dendrimers. [27,28] However, we only remineralized partially demineralized dentin and intrafibrillar remineralization was not observed due to the limitations in our detection system. In some clinical situations (i.e., hybrid layers created by etch-and-rinse adhesive systems), dentin surfaces are completely demineralized, which results in the exposure of type I collagen fibrils.…”
Section: Introductionmentioning
confidence: 56%
“…However, a previous study has demonstrated that there was nearly no cytotoxicity to oral cells when the concentration of PAMAM-NH 2 was lower than 1250 ug/mL. [28] Therefore, the concentration of PAMAM-NH 2 in this study (1000 ug/mL) was safe and could potentially be used in clinical dentistry.…”
Section: Collagen Mineralizationmentioning
confidence: 81%
“…The size and shape of HA could be regulated by PAMAM dendrimer with different surface groups, generations, and concentrations [45,46]. Liang et al found that PAMAM can serve as a mineralization template and induce dentine remineralization with superior depth, good acid resistance, and good biocompatibility [35,37]. Indeed, PAMAM was demonstrated to be an excellent nucleation template for dentine [47].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now the vast majority of the studies with dendritic derivatives addressed the mineralization of CP in bulk aqueous solution for mimicking the effect of noncollagenous proteins, that is, the water‐soluble fraction of proteins. Other studies focused on in vitro remineralization of CP‐based composites such as dentine and enamel . These studies involved various types of dendrimers such as carboxylic acid‐terminated poly(amidoamine) (PAMAM) dendrimers, amine terminated dendrimers such as PAMAM, poly(propylene imine) (PPI), and branched poly(ethylene)imine (PEI), hydroxyl‐terminated PAMAM, and phosphate‐terminated PAMAM .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies focused on in vitro remineralization of CP‐based composites such as dentine and enamel . These studies involved various types of dendrimers such as carboxylic acid‐terminated poly(amidoamine) (PAMAM) dendrimers, amine terminated dendrimers such as PAMAM, poly(propylene imine) (PPI), and branched poly(ethylene)imine (PEI), hydroxyl‐terminated PAMAM, and phosphate‐terminated PAMAM . Several other studies addressed the interaction of these and other polymers with CP crystals, mostly to evaluate the interaction of the terminal functional groups with the CP surface …”
Section: Introductionmentioning
confidence: 99%